THE INFLUENCE OF USING THE DANA APPLICATION IN TRANSACTIONS IN THE DIGITALIZATION ERA - Lisnawati Lisnawati (Journal Accounting International Mount Hope, 2026)
Digital transactions are currently growing rapidly. One widely used digital transaction tool is the DANA digital wallet application. The DANA application is widely used by people from teenagers to adults. The DANA application makes it easy for users to conduct financial transactions. This study aims to determine the impact of DANA application use on transactions in the digital era. The research method used in this study is qualitative. Based on the research conducted by the researcher, it was concluded that the use of the DANA application has a positive impact on transactions in the digital era. Using the DANA application makes it easier for users to conduct financial transactions. People can send money, receive money, withdraw money, pay for electricity tokens, buy phone credit, and much more. The DANA application also offers various investment conveniences, such as gold investment.